Dynamic changes in soil moisture in three typical landscapes of the Heihe River Basin - Gou, Qianqian; Guo, Wenting; Li, Yuda; Liu, Jing; Wang, Guohua (Frontiers in Environmental Science, 2022)
The water diversion scheme of Heihe River Basin was implemented in 2000. Herein, we investigated the dynamic changes in soil moisture content and analyzed the fundamental reasons supporting the water diversion plan in this typical inland river basin in northwest China. Accordingly, we selected three typical landscape gradients—a mountain water conservation forest belt, an artificial sand-fixing forest belt at the edge of a desert oasis, and a desert riparian forest belt in the upper, middle, and lower reaches of the Heihe River Basin, respectively. In these diverse landscapes, an environmental measuring system was used to continuously monitor the dynamic and differentiation regularity of soil moisture in the 0–160 cm layer for 5 years. The results revealed that 1) the soil moisture content in each landscape increased and varied significantly across seasons. In the upper and middle reaches, the soil moisture content was significantly higher during the growing season than in the non-growing season, whereas the lower reach displayed a converse pattern. 2) The distribution of soil moisture at various depths of soil profiles varied significantly for each landscape. As the soil depth increased, the soil moisture in the upper reach decreased. Although the deep layers (120–160 cm) could store water in the non-growing season, the stored water was consumed during the growing season. The soil moisture content in the mid-reach initially increased, later decreased, and ultimately attained its highest level at 40–60 cm; however, the soil moisture content in the lower reach increased, and reached its highest level at 120–160 cm. 3) In the upper and middle reaches, the coefficient of variation of soil moisture decreased with an increasing soil depth, whereas the lower reach exhibited a converse trend. Similarly, the coefficient of variation of soil water storage were higher during the non-growing season than during the growing season within the upper and middle reaches, whereas an opposite trend was observed in the lower reach. 4) Since the implementation of the Heihe river water diversion plan, the soil moisture content in both the upper and middle reaches have increased but that of the lower reach has fluctuated and declined, especially in the shallow depths during the growing season. The present findings imply that the lower reaches of the Heihe River may require additional water transfers during the growing season.